Exploring the fantastic : genre, ideology, and popular culture - Batzke, Ina; Erbacher, Eric; Hess, Linda M.; Lenhardt, Corinna (Lettre (Transcript (Firm)), 2018)
The fantastic represents a wide and heterogeneous field in literary, cultural, and media studies. Encompassing some of the field's foremost voices such as Fred Botting and Larissa Lai, as well as exciting new perspectives by junior scholars, this volume offers a mosaic of the fantastic now. The contributions pinpoint and discuss current developments in theory and practice by offering enlightening snapshots of the contemporary Anglophone landscape of research in the fantastic. The authors' arguments and analyses thus give new impetus to the field's theoretical and methodological approaches, its textual materials, its main interests, and its crucial findings.